G91(P) Prescribing in overweight and obese children. (12th March 2018) - Kannan, S; Storey, L; Mott, A
Abstract : Aims: Childhood obesity is a growing global health burden. Prescribing medications for this cohort has until now relied on empirical experience with no set guidelines to inform drug dose calculations. Standard body weight calculated dosages have led to supratherapeutic doses commonly being prescribed. Recent research has highlighted the need for a new body weight adjusted approach to prescribing. This project aimed to evaluate whether these recent developments are being translated into practice to provide safe and appropriate doses in children over the 91 st percentile for BMI (Body Mass Index) Methods: We chose 6 drugs (aciclovir, aminophylline, gentamicin, oromorph, paracetamol and phenytoin) that have particularly narrow therapeutic windows and a high risk of toxicity with suggested dosage adjustments based on ideal (IBW) or adjusted body weight (ABW) than actual body weight. First a prescribing exercise was carried out using case scenarios in a group of paediatricians during a departmental teaching session in a tertiary children's hospital. Next, over 4 weeks, all patients on the wards were screened for being overweight or obese. Children between the ages of 2 and 16 years with BMI over 91 st centile and on one or more of the listed drugs were included. Results: In the prescribing task we had 7 paediatricians from the level of Foundation Year 1 to Consultant. Out of the 42 individual question responses none were answered using the correct dose adjustment. In the ward-based project, none of the 13 patients identified were prescribed the correct adjusted doses of their medications using IBW or ABW. The maximum daily drug overdose was 149% for a prescription of paracetamol in an 11-year-old girl. The minimum daily drug overdose was 111%. The average daily drug overdose from what was being prescribed for obese children on the ward in this four-week window was 128%. Conclusion: We identified a lack of knowledge amongst paediatricians on prescribing in children with a BMI≥91 st percentile although the sample size was small. There must be a call for more awareness and further studies to evaluate the mechanisms of altered pharmacokinetics in overweight and obese children to guide future drug dose adjustments and formulate universal guidelines.